Model to determine the degree of housing damage for a flood affected area in Kuala Krai, Kelantan / Thuraiya Mohd … [et al.] - Mohd, Thuraiya; Hasbullah, Mohd Nasurudin; Che Pin, Siti Fairuz; Nordin, Tajul Edrus; Ismail, Dzulkarnaen (Research Management Institute (RMI), 2015)
Increasing population has resulted in an increase in the number of property ownerships. Therefore, a greater percentage of the country’s land area, often in areas that previously have been not fit for urban development and human settlement, have been taken up to cater for the need for accommodation (Eves, 2014). These increased numbers of properties, changes in water collection, flows and poor drainage system coupled with heavy monsoon rainfall, intense convection rainstorms and other local factors have caused seasonal floods in Malaysia (Chan, 1996; Eves, 2014). According to the Malaysian National Security Council [MNSC] (2015), flood is the most common type of disaster that occurs in Malaysia. Floods occur annually in Malaysia, causing damage to property and loss of life. The worst flood event in Malaysia was in December 2014 that rendered people helpless. The moving water had destructive powers that picked up and carried off bridges, houses, trees, and cars. The east coasts states of Kelantan, Terengganu and Pahang expose to annual recurrence of flood as these states are directly in the path of the seasonal monsoon season (Chan, 1996). The unprecedented flooding of December 2014 has been the worst flood event in the history of Kelantan…